THE SILAING CORN PERGEDEL TRADER: AN ANTHROPOLOGICAL REVIEW (CASE STUDY: JORONGGANTIANG, NAGARI PANYALAIAN, X KOTO DISTRICT, TANAH DATAR REGENCY): THE SILAING CORN PERGEDEL TRADER: AN ANTHROPOLOGICAL REVIEW (CASE STUDY: JORONGGANTIANG, NAGARI PANYALAIAN, X KOTO DISTRICT, TANAH DATAR REGENCY) - Rio Afrianda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2021)
Rapid population growth which is not accompanied by an increase in employment creates a socialproblem, namely unemployment. This has made many people prefer businesses in the informalsector because the informal sector has characteristics that do not require large capital and skillsin the business process. In this study, the informal sector is an organization that trades corn inJorong Gantiang, Nagari Panyalaian, X Koto District, Tanah Datar Regency. In carrying out thetrading process, the traders take advantage of the buses passing their trading area.This study aims to describe the profile of traders and to describe how traders carry out theirtrading activities every day. This study is analyzed using the gift theory proposed by MarcellMauss and the concept of reciprocity. The method used is qualitative descriptive with the datacollection techniques of observation, interviews and documentation. Selection of informants wasdone by purposive sampling.The results of this study indicate that there is an evolutionary process carried out by traders ofsilaiang corn peddlers related to their trading activities. Where there is an agreement made bytraders with bus drivers passing the area where they trade to make it easier for them in the salesprocess because they will offer their merchandise to the bus passengers so there is no need tobother looking for potential buyers anymore. The agreement made was beneficial to both parties.The driver's willingness to stop at the merchant's place is rewarded by giving the driver a mealwhile the driver is resting and promising to help the driver when the car being used is damaged inthe merchant's area. The advantages of both parties make the relationship between the trader andthe driver good. Keywords: Traders, bus drivers,Agreement,Giving